Iterative Solutions for the Differential Equation with p-Laplacian on Infinite Interval. (25th June 2021) - Zhao, Guoying; Wang, Ying
Abstract : This paper systematically investigates a class of fourth-order differential equation with p -Laplacian on infinite interval in Banach space. By means of the monotone iterative technique, we establish not only the existence of positive solutions but also iterative schemes under the suitable conditions. At last, we give an example to demonstrate the application of the main result.